Rectal ozone therapy in the treatment of pain syndrome due to Lumbar Disc Herniation - Cuello Ávila, Jesús; Dreke Freire, Sobeida; Benites García, Juan Miguel (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Lumbar disc herniation is the most frequent cause of radicular pain and reason for consultation in our setting. Rectal ozone treatment has proven to be effective because it acts on cell metabolism, producing substances capable of relieving pain through different mechanisms, since they improve the intracellular redox state. A descriptive, longitudinal, prospective study was carried out in patients with pain syndrome due to lumbar disc herniation who attended the Department of Traditional Natural Medicine of the Carlos J. Finlay Military Hospital from January 2021 to December 2022 to evaluate the effectiveness of rectal ozone therapy. The sample was 100 patients who met the inclusion criteria, they were divided into two groups. The first one received 15 sessions of ozone rectally and the second treatment with analgesics and anti-inflammatories. The male sex predominated, as well as the ages between 50 and 59 years. The group that was administered ozone had a better response and 80 % of the cases presented improvement while in the group with pharmacological treatment only 52 % had relief of symptoms, in most of the patients pain relief was verified from the sixth treatment session. There was a significant improvement in the quality of life of the patients undergoing ozone treatment and adverse reactions were minimal, although more frequent in patients with drug treatment, thus demonstrating the effectiveness of ozone therapy.